Um efeito geométrico da curvatura de Gauss - RIBEIRO, Josenilda Baia (2024)
The present work aims to study and classify the critical points of functions of two variables based on results of the Differential Geometry of curves and surfaces. The work is structured in a bibliographic research bringing various information about surface curvatures and through the geometric effect of the Gaussian Curvature classify these extremes into maximum, minimum or saddle point.